KEPUASAN PASIEN POLIKLINIK PENYAKIT DALAM TERHADAP PENGARUH WAKTU TUNGGU PELAYANAN DI RS MUHAMMADIYAH AHMAD DAHLAN KEDIRI - Adi Laksono; Hilmi Nur Widiyas Rama (CV. Adiba Aisha Amira, 2025)
Customer satisfaction is a measurement of the level of satisfaction or not based on a work result compared to the desired achievement. This study aims to measure the effect of waiting time on the level of satisfaction of patients at Muhamadiyah Ahmad Dahlan Hospital, Kediri. This research uses quantitative descriptive analysis methods and chi square tests. The total sample was 89 patients with a sampling technique using purposive sampling. Data collection includes primary data and secondary data. This research uses reliability test analysis, validity test, test and chi square test. This research showed that 24 (27%) respondents stated that their waiting time met the standard <60 minutes, while 65 (73%) respondents did not meet the standard >60 minutes. Characteristics of patient satisfaction: 44 (50%) respondents expressed satisfaction, a number of respondents were dissatisfied 45 (50%) respondents. This study shows the results of the relationship between waiting time for services and the level of satisfaction of patients at the internal medicine polyclinic at the Muhammadiyah Ahmad Dahlan Kediri Hospital. Suggestions addressed to the hospital to continue to improve quickly and responsively regarding time discipline in providing services.